Jawabanmu

2014-04-09T17:53:47+07:00
1) Left side = {(1/sinA) - sin A}*{(1/cos A) - cos A}

2) Taking LCM and simplifying, left side = {(1 - sin²A)/sin A}*{(1 - cos²A)/cos A}

= (cos²A/sin A)*(sin²A/cos A) = (sin A)(cos A)/1

3) Since 1 = sin²A + cos²A, by trigonometric identity,

Left side = {(sin A)*(cos A)}/(sin²A + cos²A)

Dividing numerator and denominator by {sin A)*(cos A)} in the above,

Left side = 1/[{sin²A/(sin A*cos A)} + {cos²A/(sin A* cos A)}]

This simplifies to:
1/[(sin A/cos A) + cosA /sin A)] = 1/[tan(A) + cot(A)] = Right side [Proved]

complicated banget, bingung bacanya
sorry :3